Employment Status Following Heart Transplantation: Data From the Danish Nationwide Social Service Payment Register During 20 years - Rikke Elmose Mols; Rikke Elmose Mols; Brian Bridal Løgstrup; Brian Bridal Løgstrup; István Bakos; Erzsébet Horváth-Puhó; Finn Gustafsson; Finn Gustafsson; Hans Eiskjær; Hans Eiskjær (Transplant International, 2024)
Most studies on vocational rehabilitation after heart transplantation (HTX) are based on self-reported data. Danish registries include weekly longitudinal information on all public transfer payments. We intended to describe 20-year trends in employment status for the Danish heart-transplant recipients, and examine the influence of multimorbidity and socioeconomic position (SEP). Linking registry and Scandiatransplant data (1994–2018), we conducted a study in recipients of working age (19–63 years). The cohort contained 492 recipients (79% males) and the median (IQR) age was 52 years (43–57 years). Five years after HTX, 30% of the survived recipients participated on the labor market; 9% were in a flexible job with reduced health-related working capacity. Moreover, 60% were retired and 10% eligible for labor market participation were unemployed. Recipients with multimorbidity had a higher age and a lower prevalence of employment. Five years after HTX, characteristics of recipients with labor market participation were: living alone (27%) versus cohabitation (73%); low (36%) versus medium-high (64%) educational level; low (13%) or medium-high (87%) income group. Heart-transplant recipients with multimorbidity have a higher age and a lower prevalence of employment. Socioeconomically disadvantaged recipients had a lower prevalence of labor market participation, despite being younger compared with the socioeconomically advantaged.